Application of Science Process Skills-Based Worksheets On The Project of Making Natural Larvicide From Areca Nut - Rahma, Siti; Rahmatullah, Saepudin; Helsy, Imelda; Aisyah, Riri (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study aims to describe the application of science process skills-based worksheets in the project of making larvicides from areca nut extract on the cognitive and psychomotor aspects of students, as well as to determine the effectiveness of areca nut extract as a larvicide. This research raised the issue of using synthetic larvicides as learning facilitated by science process skills-based worksheets. The larvicide was divided into six concentration variations. This study used a pre-experiment method with a one-shot study case design involving one experimental class, without a pretest or control class. The subjects used in this study were 36 10th grade students of MAN 2 Bandung City. Data collection used instruments in the form of science process skills-based worksheets, observation sheets, performance assessment sheets, and presentation assessment sheets. Data analysis of science process skills was done with a Likert scale assessment. The cognitive aspect of the science process skills worksheet obtained an average score of 82, with a very good interpretation, while the psychomotor aspect of students was 83, which showed a very good interpretation. It can be concluded that the use of science process skills-based worksheets can help in cognitive skills and psychomotor skills. In the larvicide making project, effective results were obtained at a concentration of 9 mL with a percentage of mosquito larvae death of 100%.